1994
DOI: 10.1530/eje.0.1310557
|View full text |Cite
|
Sign up to set email alerts
|

G-Proteins: implications for pathophysiology and disease

Abstract: This article focuses on the involvement of G-proteins in neuroendocrine secretion, cell growth and phenotype alterations. The current concept of hormonal activation of the GTPase cycle, as well as the molecular diversity of G-proteins families and receptor*G-protein*effector coupling, are described. Also described are certain G-proteins as possible proto-oncogenes and how point mutations and frame shift mutations alter G-protein function and determine the characteristics of various endocrine diseases. The arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The skeletal abnormalities which we have identified in RS are similar to those found in Albright's Hereditary Osteodystrophy (Leonard et al 1995) which is associated with endocrine disturbances and a mutation in the alpha subunit of a stimulatory G protein (Patten et al 1990). G proteins also play a role in the growth and differentiation of osteoblasts (Gordeladze et al 1994). Screening of girls with RS for biochemical and/or functional abnormalities of G proteins could be important if our findings of reduced bone mass were to have a metabolic basis.…”
Section: Discussionmentioning
confidence: 99%
“…The skeletal abnormalities which we have identified in RS are similar to those found in Albright's Hereditary Osteodystrophy (Leonard et al 1995) which is associated with endocrine disturbances and a mutation in the alpha subunit of a stimulatory G protein (Patten et al 1990). G proteins also play a role in the growth and differentiation of osteoblasts (Gordeladze et al 1994). Screening of girls with RS for biochemical and/or functional abnormalities of G proteins could be important if our findings of reduced bone mass were to have a metabolic basis.…”
Section: Discussionmentioning
confidence: 99%
“…As previously demonstrated for nuclear hormone receptors and growth factor receptors, it has been proposed that components of G protein signaling pathways may potentially be involved in the development of neoplastic and non-neoplastic human diseases (1±6, 22,23). In fact, it has been demonstrated that mutations in the genes encoding these proteins are responsible for several human diseases presenting with the clinical phenotype of hormone excess or defect.…”
Section: Abnormalities Of G Protein Signaling Pathwaysmentioning
confidence: 97%
“…Due to the ubiquitous expression of Gsa, late occurring mutations cause focal disease such as acromegaly and toxic thyroid adenomas, while when the same mutations occur very early in embryogenesis they cause disorders with widespread manifestations, such as McCune±Albright syndrome (MAS). It is tempting to speculate that activating germ-line mutations of Gsa would be incompatible with life (23).…”
Section: Gsp Oncogene In Mccune±albright Syndromementioning
confidence: 99%
“…Presumably, this is primarily due to elevation of intracellular cAMP levels, because there is abundant documentation of interactions between the cAMP and GR pathways and induction of apoptosis in lymphoid cells by both. 23,[52][53][54] The mechanism of cAMP-induced apoptosis itself is unclear, but it appears to require presence of the GR, even in the absence of exogenous glucocorticoid. 23,55 Recently published findings suggest that forskolin can stimulate p53 activity, in a pathway that appears to involve a ternary complex of p53, cAMP response element binding protein (CREB), and CREB binding protein (CBP).…”
Section: Pde4 Inhibitor Induces Apoptosis In All Cells 3395mentioning
confidence: 99%